Performance Analysis of CP-Based and CAZAC Training Sequence-Based Synchronization in OFDM System - Yudha, R. Gaguk Pratama; Astawa, I Gede Puja; Sudarsono, Amang (Politeknik Elektronika Negeri Surabaya (PENS), 2016)
Orthogonal Frequency Division Multiplexing (OFDM) is a popular wireless data transmission scheme. However, its synchronization is still being a major problem when it is applied in real hardware. Cyclic Prefix (CP) based synchronization is one of the solutions in this problem, but CP has high crest factor. In the other hand, CAZAC sequence is another solution with lower crest factor but the higher complexity and also CAZAC has potential in security and channel estimation implementation. The performance between CP and CAZAC sequence based synchronization in OFDM system is analyzed in this paper. The real hardware, Universal Software Rado Peripheral (USRP), is used to prove the analysis. The CAZAC sequence has 10% performance increased in frequency offset than CP based synchronization.